2016
DOI: 10.1016/j.mycmed.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of a Saharan strain of Actinomadura sp. ACD1 against toxigenic fungi and other pathogenic microorganisms

Abstract: A new strain of actinobacteria, designated ACD1, was isolated from a Saharan soil sample in the Hoggar region (Algeria). Morphological study led to this strain being classified as a member of the Actinomadura genus. Phylogenetic analysis based on the 16S rRNA gene showed that the strain is closely related to Actinomadura sediminis DSM 45500(T) (98.5% sequence similarity). Furthermore, strain ACD1 presented a strong activity against mycotoxigenic and phytopathogenic fungi, including Aspergillus and Fusarium str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…These authors also isolated other species of Streptomyces with Actinoplanes and Geodermatophilus from the Negev and Mojave desert soils [42]. In addition, the Algerian Saharan soil reveled the existence of several actinobacterial strains, with some of them belonging to rare genera such as Actinomadura, Nonomuraea, Nocardiopsis, Saccharothrix, Spirillospora, and Streptosporangium [43][44][45].…”
Section: Actinobacterial Diversity In Different Moroccan Extreme Envimentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also isolated other species of Streptomyces with Actinoplanes and Geodermatophilus from the Negev and Mojave desert soils [42]. In addition, the Algerian Saharan soil reveled the existence of several actinobacterial strains, with some of them belonging to rare genera such as Actinomadura, Nonomuraea, Nocardiopsis, Saccharothrix, Spirillospora, and Streptosporangium [43][44][45].…”
Section: Actinobacterial Diversity In Different Moroccan Extreme Envimentioning
confidence: 99%
“…of them belonging to rare genera such as Actinomadura, Nonomuraea, Nocardiopsis, Saccharothrix, Spirillospora, and Streptosporangium [43][44][45].…”
Section: Pgp Potentials Of Extremophilic Actinobacteriamentioning
confidence: 99%
“…Antimicrobial activity of the solvent against the test strains was not detected by the agar spot assay. Related Actinomadura actinomycetes produce several antimicrobial compounds against Clostridium perfringens S107, Clostridium difficile 630, Trypanosoma brucei brucei strain GUTat 3.1, S. aureus, Kocuria rhizophila or Proteus hauseri [24][25][26][27][28][29]. Compared with related studies, we demonstrated that strain DS-MS-114 produces an antibacterial compound against S. aureus NBRC12732 T .…”
Section: Purification Of the Antibacterial Compound And Evaluation Ofmentioning
confidence: 89%
“…However, 83/84 fractions were able to reduce mycotoxins production by >90%. Regarding fungal growth, a number of studies have shown a low percentage of extract fractions, especially from natural antifungal sources such as plant extracts or actinobacteria, were effective at controlling growth of fungal pathogens (Lahoum et al 2016;Nalubega et al 2016;Dikhoba et al 2019). However, many of these studies did not examine impacts on mycotoxin production.…”
Section: Impact Of Naja Nigricollis and N Siamensis Fractions On Mycmentioning
confidence: 99%
“…The presence of these compounds in food products is strictly regulated worldwide (European Union 2006;Wu and Khlangwiset 2010). Research has been focused on screening alternative sources of naturally produced antimicrobial compounds from extreme environments, micro-organisms and plant extracts, especially essential oils (Aldred et al 2008;Bluma et al 2008;Verheecke et al 2014;El Khoury et al 2016;Lahoum et al 2016;Mylona et al 2019;Mohd Danial et al 2020;Garc ıa-D ıaz et al 2020). However, there have been few new lead compounds which have been found for use in food and feed chains to reduce mould growth and mycotoxin contamination, without impacting on the organoleptic properties of the final product.…”
Section: Introductionmentioning
confidence: 99%